Pointwise Hypothesis Testing of Biomedical Near-Infrared Spectroscopy Signals - Gervytė, Miglė; Žvirblis, Tadas (Vilnius University Open Series, 2025)
This study uses a pointwise statistical approach to analyze Near-Infrared Spectroscopy (NIRS) signals in preterm infants with and without Patent Ductus Arteriosus (PDA). Three oxygenation signals—SpO2, rSO2-1 (cerebral), and rSO2-2 (renal)—were analyzed across no-PDA, PDA, and hsPDA groups. Smoothed signals were tested using pointwise ANOVA and Tukey HSD to detect significant group differences. Results showed distinct patterns in rSO2-1 and rSO2-2, with the hsPDA group standing out in rSO2-1 and the no-PDA group in rSO2-2, demonstrating the value of this method in biomedical signal analysis.